2008
DOI: 10.1186/ar2516
|View full text |Cite
|
Sign up to set email alerts
|

Role of STAT4 polymorphisms in systemic lupus erythematosus in a Japanese population: a case-control association study of the STAT1-STAT4 region

Abstract: Introduction Recent studies identified STAT4 (signal transducers and activators of transcription-4) as a susceptibility gene for systemic lupus erythematosus (SLE). STAT1 is encoded adjacently to STAT4 on 2q32.2-q32.3, upregulated in peripheral blood mononuclear cells from SLE patients, and functionally relevant to SLE. This study was conducted to test whether STAT4 is associated with SLE in a Japanese population also, to identify the risk haplotype, and to examine the potential genetic contribution of STAT1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 29 publications
4
74
0
Order By: Relevance
“…Considering the low LD between rs7574865 and rs7601754, their data may indicate an independent contribution from rs7601754, although independence test was not mentioned from the study. Findings from an SLE cohort in the Japanese population 18 also showed a 5% enrichment of the 'T' allele in diseased group, similar to our findings from Hong Kong Chinese and Thai. All the evidence considered, it seems that rs7601754 probably represents an independent variant associated with SLE.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Considering the low LD between rs7574865 and rs7601754, their data may indicate an independent contribution from rs7601754, although independence test was not mentioned from the study. Findings from an SLE cohort in the Japanese population 18 also showed a 5% enrichment of the 'T' allele in diseased group, similar to our findings from Hong Kong Chinese and Thai. All the evidence considered, it seems that rs7601754 probably represents an independent variant associated with SLE.…”
Section: Discussionsupporting
confidence: 89%
“…Our data on the subphenotype stratification are largely consistent with the findings by Taylor et al, 11 which we believe, with increased sample size, may provide further evidence on the stronger association of rs7574865 with severe phenotypes of the disease, such as hematologic disorder, nephritis and ds-DNA antibody production. Recently, Kawasaki et al 18 showed that rs7574865 has higher ORs with SLE patients with nephritis, anti-ds-DNA antibody production and early onset age, although none reached statistical significance, presumably due to small sample size in their study (308 cases vs 306 controls). A word of caution is that subphenotype stratification opens the door for false positives due to multiple testing, which could be overcome by comparing results from different studies, and examining the comprehensive pattern of subphenotype association.…”
Section: Discussionmentioning
confidence: 91%
“…28 Other SNPs were genotyped using the TaqMan genotyping assay (Applied Biosystems, Foster City, CA, USA), as previously described. [15][16][17][18] Identity of the genotyping results were confirmed when two genotyping systems were used for a locus.…”
Section: Genotypingmentioning
confidence: 81%
“…Thus far, we replicated association of HLA-DRB1*15:01, STAT4 rs7574865T, BLK rs13277113A, TNFAIP3 rs2230926G and TNIP1 rs7708392C in Japanese, which had previously been reported in the Caucasian or Chinese populations. [14][15][16][17][18] In the process of these studies, we noted that the genetic contribution of STAT4, BLK and TNIP1 was greater in the Japanese compared with the Caucasian populations, due to population differences in the risk allele frequencies. 15,16,18 With respect to IRF5, we found that the initially reported Caucasian risk haplotype carrying rs2004640T, exon 6 insertion and rs10954213A 19 was nearly absent in Japanese 20 Moreover, although the association of rs2004640 was also observed in Japanese, another single nucleotide polymorphism (SNP) rs41298401, which is monomorphic in Caucasians, was more strongly associated with SLE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation